2022
DOI: 10.1029/2021jb023645
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Carbon Alloy Under Shock Compression: Implications for the Carbon Concentration in Earth’s Inner Core

Abstract: Seismic and cosmochemical constraints suggest that the Earth's solid inner core primarily consists of an ironnickel (Fe-Ni) alloy with light elements, which are expected to reduce the density by 2.5%-5% with respect to pure iron (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
(162 reference statements)
1
2
0
Order By: Relevance
“…The V P of Fe 7 C 3 is slightly higher than that of Fe, and both are much larger than the PREM values. Thus, carbon might be ruled out as the major light element in the Earth's inner core, which is consistent with findings of Fe-C phase, [38] Fe-C solid solution, [39] and geochemical [40] investigations. By analyzing the Fe-C phase diagram at high temperatures and pressures, Fei et al suggested that the carbon content of the inner core is about 2.24%.…”
Section: Geophysical Implications For Inner Core Compositionsupporting
confidence: 87%
See 1 more Smart Citation
“…The V P of Fe 7 C 3 is slightly higher than that of Fe, and both are much larger than the PREM values. Thus, carbon might be ruled out as the major light element in the Earth's inner core, which is consistent with findings of Fe-C phase, [38] Fe-C solid solution, [39] and geochemical [40] investigations. By analyzing the Fe-C phase diagram at high temperatures and pressures, Fei et al suggested that the carbon content of the inner core is about 2.24%.…”
Section: Geophysical Implications For Inner Core Compositionsupporting
confidence: 87%
“…[38] More recently, Huang et al experimentally determined Fe-C solid solution densities up to core pressures, and concluded that interstitial carbon can lower the density of iron and be present in the inner core. [39] Using geochemical methods, McDonough concluded that the carbon content of the inner core is less than 0.2%. [40] Therefore, if carbon is present in the inner core, other light elements must also be present, which has inspired many studies of the Fe-C-Si ternary sys-tem.…”
Section: Geophysical Implications For Inner Core Compositionmentioning
confidence: 99%
“…The equation of state is a functional expression that describes the relationship between the state variables of a substance, and is used to express the properties of a substance under certain thermodynamic conditions [3,4]. The study of the equation of state is the key to understanding the failure mechanism of materials under strong dynamic loads, and it is also the basis for numerical calculation of dynamic responses under extreme dynamic loads such as explosions and ultra-highspeed shocks [5,6].…”
Section: Introductionmentioning
confidence: 99%